The Cirebonan Theatrical Performing Art in the Middle of Globalization Exposure - Supardan, Dadang (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2013)
This study is based on the concern of solid negligence towards the fundamental values of the Cirebonan theatrical performing arts due to the globalization exposure that affects the contra development or marginality of traditional arts. The problem formulation developed in the research includes: (1) What is the origin of the Cirebonan play performing art in the coastal areas of the West Java border? (2) What are the purposes of the art to be performed in Cirebon, a region located in the coastal areas of West Java? (3) What steps in this theatrical performing arts are to be performed and enjoyed as ordinary folk art performances? (4) What is the philosophical value of is art so that it can be contributed to history education? (5) What is an effort to be made to improve the historical awareness of local people in enjoying these performing arts regardless of the threat of marginality caused by the globalization exposure? The method used in this research is a qualitative approach combined with historical and ethnographic methods. The research results are as follows: (1) The origins of Cirebonan theatrical play performing arts around 1943 0r 1944, during the Japanese occupation in Indonesia. The origin name was Reog Sepat, then became Tonil Cahya Widodo, later on it turned into a combination of Reog Sepat and Tonil Cahya Widodo. (2) The objectives of Cirebonan theatrical play performing arts include; entertainment, telling the chronicles of particular area development, providing exemplary behavior of a hero, as well as for the preaching media, and socialization of the government programs. (3) The stages of the learning implementation include the opening music (total), gimmick scene (surprised with stage tricks, such as fireworks), opening dance; the theatrical play performances; closing, with music and the theater leader epilogue. (4) The philosophical values used for history education blend cultural and spiritual characteristics, including (a) director of interference who is not dominant: the players are free to improvise as long they still stick in from the core story. (b) the diversity of players' everyday profession, such as rickshaw drivers, domestic workers, fishers, and farmers, (c) the canvas painter's involvement in the setting screen display on the stage for a story following the episode. (5) The efforts to preserve the Cirebonan theatrical performing art; both artists and the government have tried to preserve it, is not optimal because lesser Cirebonan theatrical group got a call to perform, as well as there, are no efforts to include it as the local content in the schools' curriculum